Preparation of 4′‐Spirocyclobutyl Nucleoside Analogues as Novel and Versatile Adenosine Scaffolds. Issue 67 (4th November 2019) - Verhoeven, Jonas; De Vleeschouwer, Freija; Kong, Hanchu; Van Hecke, Kristof; Pande, Vineet; Sun, Weimei; Vos, Ann; Wu, Tongfei; Meerpoel, Lieven; Thuring, Jan Willem; Verniest, Guido
Abstract: Despite the large variety of modified nucleosides that have been reported, the preparation of constrained 4′‐spirocyclic adenosine analogues has received very little attention. We discovered that the [2+2]‐cycloaddition of dichloroketene on readily available 4′‐ exo ‐methylene furanose sugars efficiently results in the diastereoselective formation of novel 4′‐spirocyclobutanones. The reaction mechanism was investigated via density functional theory (DFT) and found to proceed either via a non‐synchronous or stepwise reaction sequence, controlled by the stereochemistry at the 3′‐position of the sugar substrate. The obtained dichlorocyclobutanones were converted into nucleoside analogues, providing access to a novel class of chiral 4′‐spirocyclobutyl adenosine mimetics in eight steps from commercially available sugars. Assessment of the biological activity of designed 4′‐spirocyclic adenosine analogues identified potent inhibitors for protein methyltransferase target PRMT5. Abstract : A novel class of chiral 4′‐spirocyclobutyl adenosine mimetics was prepared from abundant chiral pool sugars, comprising the [2+2]‐cycloaddition of dichloroketene on 4′‐ exo ‐methylene furanose substrates and Vorbrüggen nucleobase introduction in the key steps. In vitro assessment of designed SAM‐mimetics demonstrated potent inhibition for protein methyltransferase target PRMT5.